2002
DOI: 10.35536/lje.2002.v7.i1.a4
|View full text |Cite
|
Sign up to set email alerts
|

“Commenting on the Causal Factors Controlling Female Decision Making” A study of Female Decision Making Regarding Paid Employment: Punjab, Pakistan

Abstract: Introduction As societies grapple with incorporating the concepts of gender equality and gender sensitivity, female decision making is quickly losing its designation as a peripheral issue. Indeed the United Nations Division for the Advancement of Women in support of the Commission on the Status of Women has been exploring the question of women and decision making for some time. In 1997 it called upon governments to take into consideration diverse decision making styles and to enhance the images of women in pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The term "mazbootaurat" or "strong woman" when explored among this Pakistani community, appeared to be employed as a synonym for an educated woman. The higher the level of education, the stronger negotiator ("mazbootaurat") she is, and makes a better-informed decision about her children"s health, family health, children education and household purchases, a finding previously reported (Jejeebhoy & Sathar, 2001;Acharya et al, 2010;Fatima, 2014;Mumtaz & Salway, 2007;Shahnaz & Kizilbash, 2012).Education not only bestowed them with information and knowledge, but also made them a good communicator. Through this quality, women were able to disperse their thoughts and views, across their family system.…”
Section: Discussionmentioning
confidence: 89%
“…The term "mazbootaurat" or "strong woman" when explored among this Pakistani community, appeared to be employed as a synonym for an educated woman. The higher the level of education, the stronger negotiator ("mazbootaurat") she is, and makes a better-informed decision about her children"s health, family health, children education and household purchases, a finding previously reported (Jejeebhoy & Sathar, 2001;Acharya et al, 2010;Fatima, 2014;Mumtaz & Salway, 2007;Shahnaz & Kizilbash, 2012).Education not only bestowed them with information and knowledge, but also made them a good communicator. Through this quality, women were able to disperse their thoughts and views, across their family system.…”
Section: Discussionmentioning
confidence: 89%
“…Women's decision making power negatively affects child labor in a society by improving the human capital of the future generation. Influential mothers are oriented towards the education of their children and they are less likely to send their kids in the labor market (see, e.g., Shahnaz and Kizilbash 2002;Drèze and Murthi 2001;Behrman et al 1999). Thus, the functional form of the model to capture the influence of women's decision making power on child labor is specified as follows.…”
Section: Methodology and Estimation Techniquementioning
confidence: 99%
“…Some studies mainly focus on the relationship between empowered mother and child's welfare because mothers play an important role in their children's well-being when they exercise some level of influence in the process of decision making of the household (Shahnaz and Kizilbash 2002;Khan and Raza 2014;Impicciatore and Dalla Zuanna 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Education can help women to gain confidence, motivation and pave the way to uplift their status and become better citizens in contributing to the growth and development of the country. In this respect, studies like Shahnaz and Kizilbash (2002), Zafar et al (2005), Fatima (2013, and Samari and Pebley (2015) concluded that education is one of the significant determinants of women empowerment.…”
Section: Determinants Of Women's Empowermentmentioning
confidence: 99%